2023
DOI: 10.1186/s13019-023-02119-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intravenous iron for treatment of anemia before cardiac surgery: An updated systematic review and meta-analysis with trial sequential analysis

Abstract: Background Preoperative anemia is common in patients undergoing cardiac surgery with various etiologies, among which iron deficiency is the leading cause. However, the benefit of intravenous (IV) iron for the treatment of anemia before cardiac surgery is uncertain. This updated meta-analysis aimed to evaluate the efficacy of IV iron in adult cardiac surgery patients with preoperative anemia. Methods This review was conducted according to Preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Recent studies have shown conflicting evidence. In a meta-analysis evaluating 936 patients with anemia in the preoperative setting for cardiovascular surgery, IV iron did not reduce the transfusion requirements but was associated with decreased mortality (62). On the other hand, the PREVENT trial, found no difference between groups in terms of red cell transfusion and 30-day mortality, despite observing a beneficial effect on the Hb in the iron group.…”
Section: Ironmentioning
confidence: 94%
“…Recent studies have shown conflicting evidence. In a meta-analysis evaluating 936 patients with anemia in the preoperative setting for cardiovascular surgery, IV iron did not reduce the transfusion requirements but was associated with decreased mortality (62). On the other hand, the PREVENT trial, found no difference between groups in terms of red cell transfusion and 30-day mortality, despite observing a beneficial effect on the Hb in the iron group.…”
Section: Ironmentioning
confidence: 94%
“…Preoperative anemia, vitamin, and iron deficiency should be corrected preoperatively, if possible. 34,35 Although of some benefit in cardiac surgery, consideration of intravenous iron therapy to improve hemoglobin levels 36 is not well established or studied in lung transplantation. Erythropoietin has not been well studied in lung transplantation, with limitations including an unknown surgery date and cost of the drug relative to the time to clinical benefit.…”
Section: Preprocedure: Patient Selection and Optimizationmentioning
confidence: 99%
“…Additionally, blood transfusions may lead to the release of free hemoglobin and free iron as a result of hemolysis [ 6 ]. On the other hand, the benefits of intravenous iron supplementation for anemia treatment in critically ill patients are still controversial [ 42 , 43 ]. Hence, while a general positive correlation between anemia and iron content can be acknowledged, this relationship becomes more contentious when considering NBTI.…”
Section: Iron Metabolism In Critically Ill Patientsmentioning
confidence: 99%